Bimbingan Akuntansi Dan Perpajakan Dasar Bagi Binaan Yayasan Manusia Indonesia Baru – Victory Outreach Bandung - Thom Deutmar Londo Doaly; I Ketut Wenten; Alexander Raphael (Universitas Pamulang, 2022)
This Community Service (PKM) is in collaboration with Yayasan Manusia Indonesia Baru based in South Tangerang, Banten Province, Indonesia. In this activity, the team of lecturers collaborated with the management of Yayasan Manusia Indonesia Baru, which is an independent foundation with a focus on socializing the dangers of drugs and other addictions as well as providing guidance to drug users and their families. The purpose of this PKM is to help those under Yayasan Manusia Indonesia Baru prepare to enter the social stage of a career in accounting and taxation. In addition, the lecturers are also expected to motivate the assisted members of Yayasan Manusia Indonesia Baru to move forward and leave or forgeting to return to narcotics abuse activities. The management, employees and assisted members involved in this PKM are approximately 12 people with a teaching time of approximately 120 minutes offline on July 9, 2022. The methods used in the implementation of this PKM are counseling/lectures, tutorials, and online discussions. face to face. This PKM is expected to be useful for various parties including the management of Yayasan Manusia Indonesia Baru and its fostered citizens, students and academics. The socialization activity through the presentation of basic accounting and taxation guidance materials for Yayasan Manusia Indonesia Baru - Victory Outreach Bandung is one of the activities that help the community in this case, especially the inmates related to drugs, in increasing knowledge of the accounting and taxation professions that can be undertaken after completion of the rehabilitation process.